Tribalism and Radicalisation: A Critical Review on Marketing and Branding Practices in Developing Social Cohesion - Bandara, Saumya; Dissanayake, Ravindra (Technium Social Sciences Journal, 2021)
Branding is extendedly connected with consumers, and multiple engagements are found in the literature explaining how brands connect to human life. Brand community or tribalism is a vastly discussed phenomenon explaining how brands are engaged with consumers as a community moral. Brand community or similarly claimed brand tribalism was investigated with different consumer behavioural aspects to explain how tribalism leads to favourable brand relationship behaviours. The contemporary literature reveals the power of virtual brand communities as well. Meanwhile, the notion of radicalism signifies how consumers and brand become interconnected with exclusive bonds which sometimes exclude the commonalities in a given society. However, the tribalism and radicalism are found a fit with each other whilst arguments are reflected on radicalism against social cohesion. Alongside, this paper addresses this interesting explanation by reviewing the concept of tribalism supported by empirical evidence and theoretical associations. Additionally, the article reveals radicalisms and its influence on consumers based on cases to bridge practical evidence with empirical claims. The notion of social cohesion was discussed with its fundamentals against the explanations given on radicalism. Conclusively, paper contributed to review those concepts and organised an explanation of empirical arguments. Paper presents a discussion supported by theoretical models and conceptual models proposed by authors to synthesise the variable relationships. Finally, it concluded future research directions mentioning specific research scopes to be concerned.